SOCIAL MARKETING-MIX ELEMENTS AND DRUG ABUSE DEMARKETING IN NIGERIAN UNIVERSITIES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study examined the effect of social marketing-mix elements on youths’ drug abuse inpublic universities in Cross River State, Nigeria. The research was sparked by theobservation that marketing programs aimed at reducing the menace of drug abuseamongst university students have not been fully implemented in the State. Data werecollected from volunteered 397 students of the University of Calabar and Cross RiverState University of Technology, Nigeria, through random sampling technique, using afour-point likert scale questionnaire, and analyzed with Principal Component Analysis(PCA). The results revealed that the social marketing-mix elements (product, price, place,promotion, publics and policy) examined significantly influenced demarketing of drugabuse in public universities in Cross River State, Nigeria. Hence, it was recommendedthat social marketers,should design and package their campaigns to target audiences onthe ills of drug abuse in universities and colleges, toreflect social marketing-mixelements, so that the target audience do not feel embarrassed, criticized, withdrawn orengage in denials; and programmes aimed at demarketing drug abuse should beaffordable and accessible to the target audience.